Feeling differently: Approaches and their politics. (November 2017) - Gammerl, Benno; Hutta, Jan Simon; Scheer, Monique
Highlights: Brings together rules-based, practice-theoretical, psycho-analytical and affect-theoretical approaches. Feelings can undermine established differences, constitute difference, and mark, intensify or naturalise differences. Navigating the seeming gap between the unfathomable quality of feeling and a critical analysis is key. The polyvalent nature of feeling differently invites continued interrogations into power effects that accompany our research.